2020
DOI: 10.1016/j.bjoms.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary care doctors and dentists in the referral of oral cancer: a systematic review

Abstract: Background: Oral cancer is referred to specialists by both GPs and dentists, with varying proportions reported in different studies. However, some have also noted that dentists more frequently refer oral cancer in the absence of patient-perceived symptoms and may refer oral cancers at an earlier stage. Unfortunately, approximately half the UK adult population do not receive regular dental care.Objectives: Conduct a systematic review on studies that compare GPs and dentists in the referral of oral cancer focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Dentists should be responsible for the primary prevention of oral cancer by identifying precancerous lesions, advising on smoking cessation, alcohol diminution, and sun protection 19 . OPSCC were diagnosed in the early stages by dentists than to physicians 20,21 . Regular dental visits were also associated with diagnosis at early stages 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Dentists should be responsible for the primary prevention of oral cancer by identifying precancerous lesions, advising on smoking cessation, alcohol diminution, and sun protection 19 . OPSCC were diagnosed in the early stages by dentists than to physicians 20,21 . Regular dental visits were also associated with diagnosis at early stages 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that the percentage of medical referrals ranged from 13% to 86% and the referrals of the dentists ranged between 15% and 80% without statistical significance between the remission of one or the other on the results in the patients. 35 The present study considered the number of graduated dentists and the ratio of medical personnel in direct contact with the patient per 1000 inhabitants for the year 2019 in each of the states. The data were obtained from the National Association of Universities and Institutions of Higher Education 36 and the Secretariat of Health of Mexico, 37 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Other 28 (10) Table 1 Reasons for delay across a total of 35 patients where delay identified Fine needle aspiration cytology and soft tissue biopsy confirmed squamous cell carcinoma (SCC). They were admitted to Aintree Hospital for pain management, speech and language therapy (SALT) and dietetic assessment due to increasing dysphagia, poor nutrition and severe pain.…”
Section: Delay % Patients (N)mentioning
confidence: 99%
“…Recent studies have shown 70% of patients with mouth cancer symptoms are more likely to consult their GP rather than their GDP; however, no significant difference between GPs and GDPs in delay in referral has been reported. 10,11 When discussing delays in diagnosis of mouth cancer the majority of cases are related to patient factors; however, professional factors in both primary and secondary care also play an important role.…”
Section: Introductionmentioning
confidence: 99%